2015
DOI: 10.1016/j.jacc.2015.08.243
|View full text |Cite
|
Sign up to set email alerts
|

TCT-227 Is aspiration thrombectomy beneficial in patients undergoing primary percutaneous coronary intervention? An updated meta-analysis of randomized trials

Abstract: 2016-11-02T18:49:00

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
36
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 0 publications
3
36
2
Order By: Relevance
“…Although hyperlipidemia was not associated with MVO in the current study, a prior meta-analysis found that statin use prior to primary PCI was associated with a lower risk of no-reflow (15). Additional approaches such as aspiration thrombectomy, deferred stenting strategy, and ischemic pre-conditioning have been shown to reduce the risk of noreflow; however, the improvement in angiographic measures with these strategies did not translate into improvement in clinical outcomes (16)(17)(18). In a patient level meta-analysis of three large RCTs, aspiration thrombectomy was associated with a trend towards reduced cardiovascular mortality in STEMI patients with high thrombus burden (19).…”
mentioning
confidence: 99%
“…Although hyperlipidemia was not associated with MVO in the current study, a prior meta-analysis found that statin use prior to primary PCI was associated with a lower risk of no-reflow (15). Additional approaches such as aspiration thrombectomy, deferred stenting strategy, and ischemic pre-conditioning have been shown to reduce the risk of noreflow; however, the improvement in angiographic measures with these strategies did not translate into improvement in clinical outcomes (16)(17)(18). In a patient level meta-analysis of three large RCTs, aspiration thrombectomy was associated with a trend towards reduced cardiovascular mortality in STEMI patients with high thrombus burden (19).…”
mentioning
confidence: 99%
“…This paradoxical finding was shown in other primary PCI interventions, such as aspiration thrombectomy, where earlier small studies had illustrated improvement of multiple surrogate markers such as TIMI flow and MBG. However, subsequent larger studies that were powered for clinical outcomes, failed to show any added benefit of such interventions . Although prior meta‐analyses suggested that IPoC might be associated with improvement in post primary PCI myocardial perfusion assessed by TIMI flow and MBG, and reduction of infarct size .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the Thrombus Aspiration in ST-Elevation Myocardial Infarction in Scandinavia (TASTE) trial found no benefit of routine thrombectomy at 1 year 34. A meta-analysis of 17 trials with over 20 000 patients also failed to document a benefit of routine thrombectomy 35. In an attempt to address these conflicting results, Jolly et al 36 enrolled 10 732 patients in the Trial of Routine Aspiration Thrombectomy with PCI versus PCI Alone in Patients with STEMI (TOTAL) and found no reduction in cardiovascular events for patients randomised to routine thrombectomy.…”
Section: Acute Coronary Syndromesmentioning
confidence: 99%